(untitled) (Altre Modernità, 2019)
One of the main challenges in teaching translation between Spanish and Italian with tourist texts are culture-specific items, both for their referential role – presenting a foreign reality and therefore attractive to the travellers’ eyes– and as functional markers within the communicative context in which they are employed. Although they could be labelled as mere extralinguistic problems since they are related to cultural differences, these culture-specific items might cause other kinds of problems, related to the author’s intention, or depending on the target context and audience of the translated text, i.e. pragmatic problems. So, apart from an exahustive documentation, including out of date bilingual dictionaries –providing, for instance, extended encyclopedic information– and Linguistic Istitutional sites such as Real Academia Española–providing information about neologisms or proper use of anglicisms–, before deciding the right translation strategy for rendering them, we have to take under consideration some other factors, such as the relevance of the culture-specific item and its functions within the specific text employed, as well as the text type and genre, the relationship between the two cultures, etc. In our didactic proposal we present a hybrid text type, the editorial hotel review, written by a travel journalist of El Pais, in which culture-specific words are employed with different purposes and, as a consequence, translation tecniques may vary. Finally, we will underline the relevance of the translator’s "internalised culture" of the language from which he/she translates, as well as his/her intercultural competence who helps to convey the functions of culture-specific items without forgetting the needs of the target audience and always keeping in mind that practical employment of the translated tourist text.